Lifestyle and Religiousity of Employees of The Kyai Syarifuddin Lumajang Foundation Regarding Interests in Using Sharia Financial Institutions - Umila, Titin; Umi Suswati Risnaeni; Muhammad Farid; Shinta Nuriah Ramadani (Muhasabatuna : Jurnal Akuntansi Syariah, 2024)
Recent trends in the financial sector and services increasingly emphasize the importance of financial literacy. The 2019 National Survey of Financial Literacy and Inclusion (SNLIK) showed a financial literacy index of 38.03% and a financial inclusion index of 76.19%. This shows that Indonesian society in general does not yet properly understand the characteristics of various financial products and services offered by formal financial service institutions, even though financial literacy is an important skill in the context of community empowerment, individual welfare, consumer protection and increasing financial inclusion. Apart from financial literacy which must be improved, people's lifestyles also need to be known, because lifestyles related to money will influence a person's economic behavior. Economic behavior is also greatly influenced by a person's level of faith. The aim of this research is: to explore the influence of sharia financial literacy of Kyai Syarifuddin Foundation employees on their interest in using financial institutions. Sharia. to explore the influence between the lifestyle of Kyai Syarifuddin Foundation employees on their interest in using Sharia Financial Institutions. To explore the influence between the religiosity of Kyai Syarifuddin Foundation employees on their interest in using Sharia Financial Institutions. This research uses quantitative methods. Data collection techniques use documentation and questionnaires. The data analysis uses Multiple Linear Regression. The conclusion of this research: There is a partial influence by the Islamic financial literacy variable on interest in using Sharia Financial Institutions. There is a partial influence by lifestyle variables on interest in using Sharia Financial Institutions. There is no partial influence of the religiosity variable on interest in using Sharia Financial Institutions.